Defense Mechanisms in E. A. Poe's Selected Short Stories the Black Cat & the Tell-Tale Heart - Rasynal Tenrisanna (ELS Journal on Interdisciplinary Studies in Humanities, 2018)
Defense mechanism is strategies the ego uses to defend itself against the anxiety provoked by conflicts. The aim of the research is to describe the types of defense mechanism in two of Poe’s selected short stories, The Black Cat & The Tell-Tale Heart & to reveal the implementation of characters’ mechanism in solving the conflicts. The research employed a descriptive qualitative method with a psychoanalysis approach Sigmund Freud’s theory of defense mechanism. The data constitute both primary & supporting data. The primary data derived from E. A. Poe’s Selected Short Stories The Black Cat & The Tell-Tale Heart, while the supporting data were taken by means of library research mainly from books, theses, dissertation, electronic articles & journals. The results show that the characters have performed a range of defense mechanisms in Poe’s selected short stories. In The Black Cat & The Tell-Tale Heart stories, the characters are mainly concerned with repression, denial, reaction formation, rationalization, displacement of self-defense. These characters performed a range of defense mechanism in order to resolve the conflicts.